Peningkatan Manajemen Wisata Berbasis Eco-Smart Tourism sebagai Upaya Pembangunan Berkelanjutan: Improving Eco-Smart Tourism Management as a Strategy for Sustainable Development - Firdasari, Firdasari; Lisa, Nova Purnama; Lydia, Ellida Novita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The development of ecotourism-based tourism has emerged as an effective strategy to utilize local resources to boost the economy of local communities. Community-based ecotourism encourages active participation from residents, leveraging their knowledge of natural assets as tourist attractions. Active community involvement in managing tourism destinations, from planning to implementing ecotourism activities, is key to preserving these natural resources while enhancing their economic value as tourist attractions. This approach ensures that environmental sustainability is maintained, and economic benefits are directly experienced by the community.